St. Mary's Collegiate Church, Youghal, south transept, wooden screen, door jamb - O'Donovan, Danielle (My University, 2008)
Door jamb of wooden screen in south transept. From intrados, moulding comprises: quadrant, fillet, ogee.
Wooden screen
Keywords: quadrant; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Youghal (Cork, Ireland); Collegiate churches; Wooden sculpture; Late Medieval; moldings, hollow; roll moldings; moldings, ogee